The Framework of Food Security and The Food Security Ecosystem: Tawhidi Perspective - Hasun, Farda; Tanjung, Hendri; Wiryono, Sudarso Kaderi; Choudhury, Masudul Alam (International Journal of Halal Research, 2021)
The world is facing an increasing number of people who suffer from hunger, which could be worse because of unpredictable future of Covid-19. The question is how to improve the food security level of the world countries. This paper aims to develop the concept of food security, the food security framework and the food security ecosystem using Tawhidi methodology. Based on Tawhidi methodology, a problem and its solution are defined in the frame of Tawhidi world view, that is Qur’anic verses and/or sunnah of Rasulullah Muhammad PBUH as the transmission mechanism and explanation of Qur’anic verses, and/or the lower sources of Islamic knowledge. The study shows that special attention to the poor household and micro-firms, together with moderate-halal-thoyyib consumption - with encouragement to consume local product, efficient production without harming the environment at adequate capacity to produce quality products, encouraging the market operates based on market mechanism, prohibiting riba-based financing and defining the clear role of the government are clear strategy of Islam to achieve food security. The framework of food security and the food security ecosystem resulted from this study are expected to give another perspective used by stakeholders to find the solution of food security problems.